Analisis Keandalan Sistem Distribusi 20 kV dengan Metode FMEA pada Penyulang Akasia dan Lele PT PLN (Persero) ULP Kota Barat - Lestari, Citra Afri; Zulfahri, Zulfahri; Situmeang, Usaha (SainETIn : Jurnal Sains, Energi, Teknologi, dan Industri, 2021)
The level of reliability of a distribution system is very important to ensure the continuity of electricity supply to consumers. This final project was made with the aim of calculating the reliability index using the Failure Modes And Effects Analysis (FMEA) method. This research was conducted on Akasia Feeders and Lele Feeders at PT. PLN (Persero) ULP Kota Barat Pekanbaru.The existing condition of the Akasia Feeder in 2019 obtained SAIFI results of 6,419 disturbances/customers and in 2020 it was 2,814 disturbances/customers. While the 2019 Lele Feeder obtained SAIFI results of 5,005 disturbances/customers and in 2020 it was 2,196 disturbances/customers. While the SAIDI Akasia Feeder results in 2019 were 353,329 minutes/customer and in 2020 it was 105,080 minutes/customer. While the 2019 Lele Feeder obtained SAIDI results of 270,191 minutes/customer in 2020 of 111.424 minutes/customer. Considerable savings after maintenance at the Akasia Feeder and Lele Feeder. From the calculation obtained savings of Rp. 41,215,943.94 on Akasia Feeder and Rp. 10,806,099.21 on Lele Feeder for one year. The results obtained after repair efforts by scrounging trees to a safe distance for the network carry out routine network infections, so that they can more quickly map out disturbances to feeders. Limiting the number of customer outages by installing reclosers, LBS and sectionalizers. Based on the evaluation results, these two feeders are categorized as reliable, because they are below the standard value that has been determined.